2021
DOI: 10.1111/aphw.12318
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effects of a social media‐based intervention on the physical and mental health of remotely working young software professionals: A randomised controlled trial

Abstract: The present study aimed to explore the short term effects of a social media-based intervention on the physical and mental health of the software professionals working remotely during the pandemic. Sixty software professionals with poor physical and mental health were randomised to Facebook-based intervention (FIIT) and a control (CONT) group for 2 months. Forty-six remote workers (26.25 ± 3.49 years) completed the study (FIIT = 22; CONT = 26). All the respondents had the median sitting time (7.07 ± 2.30 h/day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The purpose of this study was to test the hypothesis that switching to working from home during the COVID-19 instance, a study of 1,642 adults in Cyprus showed that participants who were able to transition to working from home while still receiving their regular salaries had the lowest symptoms of anxiety and depression 34) . Finally, a randomized controlled trial of a social media-based intervention for employees working at home demonstrated significant improvements in stress, anxiety, and depression scores, suggesting that short-term virtual interventions may be effective for improving the physical and mental health of those working from home 35) . These data suggest that given adequate organizational or institutional support, the effect of working from home on workers' mental health can be buffered.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to test the hypothesis that switching to working from home during the COVID-19 instance, a study of 1,642 adults in Cyprus showed that participants who were able to transition to working from home while still receiving their regular salaries had the lowest symptoms of anxiety and depression 34) . Finally, a randomized controlled trial of a social media-based intervention for employees working at home demonstrated significant improvements in stress, anxiety, and depression scores, suggesting that short-term virtual interventions may be effective for improving the physical and mental health of those working from home 35) . These data suggest that given adequate organizational or institutional support, the effect of working from home on workers' mental health can be buffered.…”
Section: Discussionmentioning
confidence: 99%
“…All 25 articles included in this review were RCTs published from 2020 to 2022 in seventeen countries, including the United Kingdom ( n = 3; Gilbody et al, 2021; Liang et al, 2022; Wadhen & Cartwright, 2021), China ( n = 2; Rong et al, 2021; Wong et al, 2021), Israel ( n = 2; Gidron et al, 2021; Shapira et al, 2021), Switzerland ( n = 1; Brog et al, 2022), Australia ( n = 1; Bryant et al, 2022), Italy ( n = 1; Carbone et al, 2021), Spain ( n = 2; Catuara‐Solarz et al, 2021; Puertas‐Gonzalez et al, 2022), Germany ( n = 3; Heckendorf et al, 2022; Preuss et al, 2021; Wilke et al, 2022), the United States of America ( n = 1; Kahlon et al, 2021), Malaysia ( n = 1; Kim, 2020), New Zealand ( n = 1; Loveys et al, 2021), India ( n = 2; Muniswamy et al, 2021; Pal et al, 2022), Sweden ( n = 1; Pellas et al, 2021), Serbia ( n = 1; Vukčević Marković et al, 2020), Korea ( n = 1; Yi & Yim, 2021), Canada ( n = 1; Beauchet et al, 2022), and Turkey ( n = 1; Tekin & Cetisli‐Korkmaz, 2022). The characteristics of the 25 studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies will provide more definitive conclusions by leveraging state-of-the-art short-term longitudinal designs (e.g., experience sampling, B. or panel data (e.g., van Zoonen & Banghart, 2018), ideally combined with social media logging data (e.g., Johannes et al, 2021;Yang et al, 2021). Field experiments that vary, e.g., the amount of remote work or personal social media use during work hours represent another important avenue to improve validity of causal conclusions (e.g., Muniswamy et al, 2021). Should researchers seek to test (competing) causal mechanisms that mediate the effects of social media use on well-being at the work-home interface, they need to move beyond the currently dominating but limited cross-sectional mediation analyses (e.g., Kline, 2015;Rohrer et al, 2021).…”
Section: Limitations and Recommendationsmentioning
confidence: 99%